Early onset of heavy rainfall on the northern coast of Ecuador in the aftermath of El Niño 2015/2016 - Pineda, Luis E.; Changoluisa, Juan A.; Muñoz, Ángel G. (Frontiers in Earth Science, 2023)
In January 2016, a high precipitation event (HPE) affected northwestern Ecuador leading to devastating flooding in the Esmeraldas' River basin. The HPE appeared in the aftermath of the 2015/16 El Niño as an early onset of heavy rainfalls, normally expected in the peak-rainy season, Mar-Apr. Using gauge data, satellite imagery and reanalysis we investigate the HPE atmospheric setting and the 'weather-within-climate' characteristics of the growing-season rainfall in Dec-Jan.The unusual convective environment in late January 2016 involved local and synoptic drivers leading the development of a mesoscale convective complex (MCC) during nighttime on 24th January. The genesis of the MCC was related to an early-arriving thermal weather state and orographic lifting; the Andean ranges acted as both a channel boosting upslope flow and convective updrafts, and as a heavy-rain divide for inner valleys. The synoptic controls were associated with i) a southern boundary of the inter-tropical convergence zone, abnormally displaced to 4°N as response to the 2015/16 El Niño where eastward air surges merge upward vertical mass fluxes, ii) the arrival to the Ecuadorian coast of an equatorially-propagating Kelvin wave, and iii) a low-mid level moisture influx coming from the Amazon associated with ascent due to changes in the Walker circulation. Lastly, we suggest that the convective environment in late January could also be favored by cross-time-scale interference of the very strong El Niño event and a strong and persistent Madden-Julian oscillation (MJO) in the central Pacific.